Implementation of STEM Approach to Raise Students' Sustainability Awareness in Science Learning: A Systematic Study - Raida, Sulasfiana Alfi (Education, Science, and Technology International Conference, 2025)
The STEM approach is considered relevant to integrate scientific, social, and sustainability value dimensions in science education. This study is a Systematic Literature Review (SLR) that aims to identify and analyze STEM-based learning strategies in science learning that contribute to increasing students' sustainability awareness. The analysis was conducted on 31 selected articles from 2015–2025 using the PRISMA protocol and qualitative thematic analysis. The results of the study showed five dominant strategies: Project-Based Learning (PjBL), Problem-Based Learning (PBL), Engineering Design Process (EDP), inquiry-based and interdisciplinary learning, and ESD integration in the STEM curriculum. The sustainability indicators identified include: 1) sustainability practice awareness, 2) behavioral and attitude awareness, and 3) emotional awareness. The implementation of these strategies has proven effective in increasing students' scientific literacy, emotional engagement, and reflective attitudes towards environmental issues. These findings provide insights for the development of STEM-based science education that is contextual, reflective, and transformative in supporting sustainable development goals.